Physiological Performance and ‘Productivity of Quail’ Production Period with Addition Moringa Leaf Flour (Moringa oleifera L.) in Feed - Yohanes Baptisto Nambut; Niken Ulupi; Hera Maheshwari (Institut Pertanian Bogor, 2025)
Moringa leaf powder is a processed product derived from the Moringa tree (Moringa oleifera L.). It contains a rich source of phytonutrients that are effective antioxidants that enhance the health status of humans and livestock. This study assesses quails' physiological performance and productivity during the production period when supplemented with Moringa leaf powder in their feed. The measured parameters include hematological values, stress indicators, performance, and egg chemical quality. The ‘study used 120 female’ quails aged 7 weeks, reared for 4 weeks. A Completely Randomized Design (CRD) was employed, consisting of four levels of dietary treatments and three replications. The supplementation of Moringa leaf flour was administered through feed for 28 days at each treatment level. ‘Data were analyzed using’ ANOVA (Analysis of Variance) and descriptive analysis. The results indicated that the addition of Moringa leaf flour in feed could maintain physiological performance, improve health status, reduce cholesterol levels in egg yolk, and increase iron (Fe) content in egg yolk. The best results in this study were obtained at a supplementation level of 7.5% Moringa leaf flour. The conclusion of this study is that Moringa leaf flour is feasible as a feed supplement at a dosage of up to 7.5%. Keywords: antioxidant, cholesterol level, egg yolk, feed supplement, stress indicator